2019
DOI: 10.3390/cancers11121890
|View full text |Cite
|
Sign up to set email alerts
|

Role of Postoperative Complications in Overall Survival after Radical Resection for Gastric Cancer: A Retrospective Single-Center Analysis of 1107 Patients

Abstract: Background: The aim of this study was to investigate the impact of postoperative complications on overall survival (OS) after radical resection for gastric cancer. Methods: A retrospective analysis of our institutional database for surgical patients with gastroesophageal malignancies was performed. All consecutive patients who underwent R0 resection for M0 gastric cancer between October 1972 and February 2014 were included. The impact of postoperative complications on OS was evaluated in the entire cohort and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
(45 reference statements)
1
10
0
4
Order By: Relevance
“…The same patient collective has recently been investigated regarding the impact of postoperative complications on overall survival. The results showed that postoperative complications are a significant risk factor for poor overall survival, an effect which was mainly caused by complication-associated early mortality [9]. A further objective of the present study was to examine whether-as expected in view of the medical progress-postoperative complications and failure to rescue after gastric cancer surgery were reduced over the course of the four decades studied.…”
Section: Introductionmentioning
confidence: 78%
“…The same patient collective has recently been investigated regarding the impact of postoperative complications on overall survival. The results showed that postoperative complications are a significant risk factor for poor overall survival, an effect which was mainly caused by complication-associated early mortality [9]. A further objective of the present study was to examine whether-as expected in view of the medical progress-postoperative complications and failure to rescue after gastric cancer surgery were reduced over the course of the four decades studied.…”
Section: Introductionmentioning
confidence: 78%
“…A reduction in perioperative mortality has been observed in recent years. However, procedure-associated morbidity remains high and this is a relevant issue for patients and treatment teams [19,20]. The fact that much older and severely co-morbid patients, as well as patients in advanced tumor stages and with compromised performance status are resected might partly explain this fact [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…3 The 5-year survival rate of patients with positive peritoneal lavage cytology is approximately 12%, and the median survival time of patients with peritoneal metastasis is approximately 6-7 months. 4,5 However, the sensitivity of gastric cancer peritoneal metastasis imaging and tumour marker detection is low. Therefore, the need to find sensitive diagnostic markers of gastric cancer with peritoneal metastasis is urgent.…”
Section: Introductionmentioning
confidence: 99%